2022
DOI: 10.1136/bmjgast-2021-000822
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 1-year mortality among patients with decompensated cirrhosis: results of a multicentre evaluation of the Bristol Prognostic Score

Abstract: ObjectiveChronic liver disease continues to be a significant cause of morbidity and mortality yet remains challenging to prognosticate. This has been one of the barriers to implementing palliative care, particularly at an early stage. The Bristol Prognostic Score (BPS) was developed to identify patients with life expectancy less than 12 months and to act as a trigger for referral to palliative care services. This study retrospectively evaluated the BPS in a cohort of patients admitted to three Scottish hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Healthcare practitioners should concentrate on refining the lines of communication between patients and doctors to effectively address concerns and rectify misconceptions surrounding various treatments. 26 , 27 Moreover, the inclusion of family members in the treatment regimen can wield a positive influence on patient adherence. This inclusion might encompass educating family members on the significance of treatment adherence, accentuating their supportive role, and cultivating an environment conducive to sustained compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare practitioners should concentrate on refining the lines of communication between patients and doctors to effectively address concerns and rectify misconceptions surrounding various treatments. 26 , 27 Moreover, the inclusion of family members in the treatment regimen can wield a positive influence on patient adherence. This inclusion might encompass educating family members on the significance of treatment adherence, accentuating their supportive role, and cultivating an environment conducive to sustained compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The Bristol Prognostic Score was specifically developed to identify patients with decompensated cirrhosis at high risk of 1-year mortality, but a validation study found it has suboptimal sensitivity. 27 Standardised criteria based on patient characteristics (CTP 'C' status, multiple short-term liver-related admissions, current alcohol use in alcohol-related cirrhosis, unsuitability for transplantation and poor performance status) have been shown to predict high 1-year mortality, 28 but implementation of these criteria was only associated with a modest (33%) uptake of referral to PC. 29 Tandon et al 30 employed a functional assessment score (MELD + age + Karnovsky Performance Status) but it is arguable that our HepatoCare referral criteria are more intuitive for those experienced in the care of patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Newer scores and criteria have been developed in this area but they are variably effective. The Bristol Prognostic Score was specifically developed to identify patients with decompensated cirrhosis at high risk of 1‐year mortality, but a validation study found it has suboptimal sensitivity 27 . Standardised criteria based on patient characteristics (CTP ‘C’ status, multiple short‐term liver‐related admissions, current alcohol use in alcohol‐related cirrhosis, unsuitability for transplantation and poor performance status) have been shown to predict high 1‐year mortality, 28 but implementation of these criteria was only associated with a modest (33%) uptake of referral to PC 29 .…”
Section: Discussionmentioning
confidence: 99%